Reflections in the literature on the performance of nursing to prevent obstetric violence in primary care (Research, Society and Development, 2022)
This research aims to search, based on the scientific literature, the main concepts, and practices of obstetric violence, emphasizing the importance of the nurse's role in the prevention of this practice with an emphasis on qualified and effective prenatal care. This is an integrative literature review carried out in the main databases, where the studies found in Portuguese were read and with a time frame of five years (2017-2022), and after analysis, 15 articles were selected for sampling. Final. Regarding obstetric violence and nursing care aimed at preventing this practice, it is essential to conceptualize about the practices of violence that occur prepartum, delivery and puerperium (PPP). We emphasize the importance of health professionals offering quality, effective, individual, and humanized care, solving and clarifying all doubts and legal rights that are guaranteed by law to pregnant women and their companions, in addition to reinforcing the need for a trained team that knows how to handle, identify and intervene in V.O. From this, the need for actions aimed at education to face obstetric violence by nurses is reinforced and it is expected that the analysis of the topic in question will serve as a subsidy to lead to public guidelines and policies that are carried out by professionals against violence to obtain satisfactory results regarding the safety of these women and the reduction of these practices, the development and training of these teams.